1994
DOI: 10.1016/0378-5955(94)90114-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of AMPA selective glutamate receptor subunits in the rat cochlea

Abstract: The localization of subunits of the alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) selective glutamate receptor, termed Glutamate receptor (GluR) was examined in the rat cochlea using affinity purified polyclonal antibody to GluR subunits (GluR 1-4). GluR 2/3 and GluR 4 immunoreactive (IR) staining was observed in rat spiral ganglion cells, while GluR 1 IR was not. GluR 4 IR staining was also seen in puncta at inner and outer hair cell bases. These results suggest that GluR 2/3 and GluR 4 are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 37 publications
3
24
0
Order By: Relevance
“…Several other neurotransmitter receptors have been reported to be expressed in both vestibular and cochlear hair cells, including AMPA receptors (Devau et al, 1993;Kuriyama et al, 1994;Demêmes et al, 1995;Matsubara et al, 1996;Knipper et al, 1997), the muscarinic receptor m3 (Safieddine et al, 1996), and ␣9 nicotinic receptors (Elgoyhen et al, 1994). None of these receptors is found solely expressed in IHCs of the organ of Corti.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Several other neurotransmitter receptors have been reported to be expressed in both vestibular and cochlear hair cells, including AMPA receptors (Devau et al, 1993;Kuriyama et al, 1994;Demêmes et al, 1995;Matsubara et al, 1996;Knipper et al, 1997), the muscarinic receptor m3 (Safieddine et al, 1996), and ␣9 nicotinic receptors (Elgoyhen et al, 1994). None of these receptors is found solely expressed in IHCs of the organ of Corti.…”
Section: Discussionmentioning
confidence: 91%
“…Accumulating evidence suggests that fast excitatory synaptic transmission in the cochlea is mediated by an excitatory amino acid. The strongest evidence supporting this hypothesis is the expression of f unctional glutamate receptors by SGNs and their localization postsynaptic of the hair cell synapse (Bledsoe et al, 1981;Puel et al, 1991a,b;Ryan et al, 1991;Safieddine and Eybalin, 1992b;Kuriyama et al, 1994;Niedzielski and Wenthold, 1995). Although glutamate is present in hair cells, and its release from hair cells is stimulated by K ϩ in a Ca 2ϩ -dependent manner (Jenisson et al, 1985;Bobbin et al, 1990Bobbin et al, , 1991Kataoka and Ohmori, 1994; for review, see Eybalin, 1993), some studies suggest that a novel excitatory amino acid may be f unctioning at this synapse (Sewell and Morz, 1987).…”
Section: Abstract: Cochlea; Vestibular End Organ; Hair Cells; Spiralmentioning
confidence: 95%
See 1 more Smart Citation
“…Although punctate immuno¯uorescence labeling was found for AMPA-type receptors around the OHC base (Kuriyama et al 1994), a lack of immunogold labeling was found in another study (Matsubara et al 1996). This suggests that glutamate receptors of this type, if they are present at all, are at low density.…”
Section: Fig 5 Graphs Based On the Preliminary Analysis Of Completementioning
confidence: 93%
“…There is also evidence that all spiral ganglion neurons, including those innervating OHCs, express a range of glutamate receptors (Niedzielski and Wenthold 1995). However, there are con¯icting reports as to whether the a-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) type GluR4 receptor subunit found at IHC synapses is also present at those of the OHCs (Kuriyama et al 1994;Matsubara et al 1996).…”
Section: Introductionmentioning
confidence: 99%